2014
DOI: 10.1080/10691898.2014.11889712
|View full text |Cite
|
Sign up to set email alerts
|

Using Work Samples from the National Assessment of Educational Progress (NAEP) to Design Tasks that Assess Statistical Knowledge for Teaching

Abstract: Statistics courses for prospective teachers are being developed in response to recent K-12 curriculum recommendations. As these courses are developed, it is important to design accompanying assessments. This manuscript describes a strategy for assessing aspects of statistical knowledge for teaching. The strategy involves analyzing and responding to children's work samples from the National Assessment of Educational Progress. An example is provided to illustrate how such an assessment task can serve to reveal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 25 publications
(20 reference statements)
0
15
0
Order By: Relevance
“…Only 26% of their participants were able to make general statements and suggest improvements. Groth (2014) found that 85% of his participants were able to identify a student with a more sophisticated response about which measure of center to use; however, the majority of his participants were not able to give specific suggestions to the less sophisticated students on improving his understanding. Ijeh (2013) found that most of his participants taught the subject of statistics, particularly graphical representations of data, in a step-wise procedural fashion and linked that teaching to student misconceptions about graphical displays, analysis, and interpreting of scatter plots.…”
Section: Statistical Education Of Teachersmentioning
confidence: 96%
See 4 more Smart Citations
“…Only 26% of their participants were able to make general statements and suggest improvements. Groth (2014) found that 85% of his participants were able to identify a student with a more sophisticated response about which measure of center to use; however, the majority of his participants were not able to give specific suggestions to the less sophisticated students on improving his understanding. Ijeh (2013) found that most of his participants taught the subject of statistics, particularly graphical representations of data, in a step-wise procedural fashion and linked that teaching to student misconceptions about graphical displays, analysis, and interpreting of scatter plots.…”
Section: Statistical Education Of Teachersmentioning
confidence: 96%
“…Like Godino et al (2008), Groth (2012Groth ( , 2014, Mercimek and Erbas (2017), and Sorto and White (2004) also worked with PSTs. Groth (2012) used writing prompts to help asses and develop content and pedagogical knowledge of his students.…”
Section: Research On Teacher's Statistical Knowledge For Teachingmentioning
confidence: 97%
See 3 more Smart Citations